COMMUNITY EMPOWERMENT THROUGH THE COMMUNITY-BASED DRINKING WATER AND SANITATION PROVISION PROGRAM (PAMSIMAS) IN NAGARI PANGIAN, LINTAU BUO DISTRICT - Vira Andani; Sitti Rahmah (Yayasan Wayan Marwan Pulungan, 2024)
The aim of this research is to determine the smoothness of the Community-Based Drinking Water and Sanitation Provision Program in Nagari Pangian, Lintau Buo District, Tanah Datar Regency so that the Pamsimas program can provide optimal distribution to the community. The type of research used is qualitative research with a descriptive approach. Data was obtained from this research by interviews, observation and documentation. Based on the results of studies in the field and then analyzed using indicators, the planning process has not run optimally, where the goal setting and actors involved have not been planned and implemented well, and there has not been a policy made by the village regarding empowerment. Pamsimas, the collection of resources in the management of Pamsimas in Nagari Pangian has not gone well, seen from the lack of human resources, there are still people who do not participate in paying monthly fees and there is damage to Pamsimas facilities and infrastructure. , the management of Pamsimas has not been carried out well, namely under supervision. There is no written report on the management of Pamsimas and guaranteeing community participation in monitoring the Pamsimas program. And there are still inhibiting factors that cause the program not to run as expected.